Taxonomic status of Pennatula argentina Acuña & Zamponi, 1992 (Cnidaria: Octocorallia) - Pérez, C. D.; Silva, B. T. (Zootaxa, 2003)
This is a taxonomic study of the species Pennatula argentina Acuña & Zamponi, 1992. The paratype is redescribed with reference to a number of characters: polyps arising directly from the rachis; the presence of polyps in oblique rows; adjacent polyps fused at the base; polyps non-retractile; absence of calyces; absence of sclerites except for minute ovals and circles in the interior of the stalk; and a robust peduncle with prominent bulb. The material is here identified as Anthoptilum grandiflorum (Verrill, 1879). Therefore, Pennatula argentina is considered a junior synonym of Anthoptilum grandiflorum.